Clinically available low intensity ultrasound devices do not promote axonal regeneration after peripheral nerve surgery: a preclinical investigation of an FDA-approved device - Däschler, Simeon C.; Harhaus-Wähner, Leila; Kneser, Ulrich (Frontiers in neurology, 2018)
The slow axonal regeneration and consecutive delayed muscle reinnervation cause persistent functional deficits following peripheral nerve injury, even following sufficient surgical nerve reconstruction. Preclinically, adjunct ultrasound therapy has shown to significantly accelerate nerve regeneration and thereby improve muscle function compared to nerve reconstruction alone. However, although FDA-approved and clinically well-tested ultrasound devices for other conditions such as delayed-healing fractures are available, they have not been investigated for peripheral nerve injury yet. Aiming to provide a fast clinical translation, we evaluated EXOGEN (Bioventus LLC, Durham, USA), a clinical device for low-intensity ultrasound therapy in various treatment intervals following peripheral nerve surgery. Sixty rats, randomized to five groups of twelve animals each, underwent median nerve transection and primary epineural nerve reconstruction. Post-surgically the ultrasound therapy (duration: 2 minutes, frequency: 1.5MHz, pulsed SATA-intensity: 30mW/cm2, repetition-rate: 1.0kHz, duty-cycle: 20%) was applied either weekly, three times a week or daily. A daily sham-therapy and a control-group served as references. Functional muscle testing, electrodiagnostics and histological analyses were used to evaluate nerve regeneration. The post-surgically absent grip strength recovered in all groups and increased from week four on without any significant differences among groups. The weekly treated animals showed significantly reduced target muscle atrophy compared to sham-treated animals (p=0,042), however, with no significant differences to three-times-a-week-, daily treated and control animals. The number of myelinated axons distal to the lesion site increased significantly in all groups (p0.05). A full recovery of distal latency was achieved in all groups and muscle function and CMAP recurred with insignificant differences among groups. In conclusion, the clinically available FDA-approved ultrasound device did not promote the axonal regeneration following nerve injury in comparison to control and sham groups. This is in contrast to a conclusive preclinical evidence base and likely due to the insufficient ultrasound-intensity of 30mW/cm2. We recommend the clinical investigation of 200-300 mW/cm2.
Gesehen am 04.01.2019